Brecht, a Grande Guerra e a "Legende vom toten Soldaten" - Teixeira, Maria Antónia Gaspar (2014)
Following a brief introduction to the euphoria that seems to have overtaken the German literary and cultural scene at the beginning of the Great War, this paper will focus on the controversial figure of young Brecht and his poem Legende vom toten Soldaten. It will be argued that Brecht, already determined to break conventions, subverted not only old subgenres of literary tradition but also motifs and images of the Christian tradition, thus producing one of the most violent documents of literary rebellion against the Great War and against war in general.